Expanding the Role of Early Health Economic Modelling in Evaluation of Health Technologies; Comment on "Problems and Promises of Health Technologies: The Role of Early Health Economic Modeling" - Carlo Federici; Aleksandra Torbica (Kerman University of Medical Sciences, 2021)
In this commentary, we discuss early stage assessments of innovative medical technologies both in terms of methods applied as well as their use in healthcare decision-making. We argue that cost-effectiveness alone may be too reductive if taken as the only decision rule, and it would benefit from being used within a broader evaluation framework. We discuss innovative methods which may contribute to better estimate the potential costs and consequences of a technology in the absence of solid clinical data, as frequently the case in early assessments. Finally, we comment on the potential synergies which may take place should early economic models be used not only by technology developers alone but as a negotiating base during early dialogues with health technology assessment (HTA) bodies.